Nucleobases in molecular recognition: molecular adducts of adenine and cytosine with COOH functional groups - Perumal, Sathiamurthi; Suresh, E.; Pedireddi, V. R. (Angewandte Chemie International Edition, 2005)
Keywords: carboxylic acids; hydrogen bonds; molecular recognition; nucleobases; supramolecular chemistry

Molecules to supermolecules and self assembly: a study of some cocrystals of cyanuric acid - Marivel, S.; Suresh, E.; Pedireddi, V. R. (Tetrahedron Letters, 2008)
The preparation and structure elucidation of cocrystals 1a, 1b, 2a- 4a, formed from cyanuric acid (CA) and the aza-donor compounds 4,7-phenanthroline, 1,7-phenanthroline, phenazine and 1, 3 -bis(4-pyridyl) propane, respectively, have been reported. While CA forms different types of self-assembling modes-monomers (la), dimers (1b and 4a) and infinite tapes (2a and 3a)-the recognition of the constituents, however, is through a triple hydrogen-bonding pattern, consisting of an N-H center dot center dot center dot N and two C-H center dot center dot center dot O hydrogen bonds, except in 4a. (C) 2008 Elsevier Ltd. All rights reserved.

Ratiometric detection of Cr3+ and Hg2+ by a naphthalimide-rhodamine based fluorescent probe - Mahato, Prasenjit; Saha, Sukdeb; Suresh, E.; Liddo, Rosa Di; Parnigotto, Pier Paolo; Conconi, Maria Teresa; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2012)
Newly synthesized rhodamine derivatives, L1 and L2, are found to bind specifically to Hg2+ or Cr3+ in presence of large excess of other competing ions with associated changes in their optical and fluorescence spectral behavior. These spectral changes are significant enough in the visible region of the spectrum and thus, allow the visual detection. For L1, the detection limit is even lower than the permissible [Cr3+] or [Hg2+] in drinking water as per standard U.S. EPA norms; while the receptor, L2 could be used as a ratiometric sensor for detection of Cr3+ and Hg2+ based on the resonance energy transfer (RET) process involving the donor naphthalimide and the acceptor Cr3+/Hg2+-bound xanthene fragment. Studies reveal that these two reagents could be used for recognition and sensing of Hg2+/Cr3+. Further, confocal laser microscopic studies confirmed that the reagent L2 could also be used as an imaging probe for detection of uptake of these ions in A431 cells.

Recognition of Hg 2+ and Cr 3+ in physiological conditions by a rhodamine derivative and its application as a reagent for cell-imaging studies - Saha, Sukdeb; Mahato, Prasenjit; Reddy, Upendar G.; Suresh, E.; Chakrabarty, Arindam; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Inorganic Chemistry, 2012)
A new rhodamine-based receptor, derivatized with an additional fluorophore (quinoline), was synthesized for selective recognition of Hg2+ and Cr3+ in an acetonitrile/HEPES buffer medium of pH 7.3. This reagent could be used as a dual probe and allowed detection of these two ions by monitoring changes in absorption and the fluorescence spectral pattern. In both instances, the extent of the changes was significant enough to allow visual detection. More importantly, the receptor molecule could be used as an imaging reagent for detection of Hg2+ and Cr3+ uptake in live human cancer cells (MCF7) using laser confocal microscopic studies. Unlike Hg(ClO4)2 or Hg(NO3)2 salts, HgCl2 or HgI2 failed to induce any visually detectable change in color or fluorescence upon interaction with L1 under identical experimental conditions. Presumably, the higher covalent nature of HgII in HgCl2 or HgI2 accounts for its lower acidity and its inability to open up the spirolactam ring of the reagent L1. The issue has been addressed on the basis of the single-crystal X-ray structures of L1·HgX2 (X– = Cl– or I–) and results from other spectral studies.

Recognition of Hg2+ion through restricted imine isomerization: crystallographic evidence and imaging in live cells - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Suresh, E.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic Letters, 2012)
A newly synthesized imine-based receptor (L) showed remarkable specificity toward the Hg2+ ion in aqueous media over other metal ions. Coordination of L to Hg2+ induces a turn-on fluorescence response. This was explained based on the restricted imine isomerization along with PET on coordination to Hg2+. X-ray structural evidence tends to favor a C–C bond rotation rather than C═N isomerization for adopting a favorable conformation in L for coordination to Hg2+. This reagent could be used for imaging the accumulation of Hg2+ ions in HeLa cells.

First demonstration of two-step FRET in a synthetic supramolecular assembly - Suresh, Moorthy; Mandal, Amal Kumar; Suresh, E.; Das, Amitava (Chemical Science, 2013)
We report a trichromophoric pseudorotaxane (3NPC) that demonstrates a two-step FRET-based relay comprising of primary donor–primary acceptor/secondary donor–secondary acceptor pairs. To achieve this, naphthalene (1) and coumarin (3) were used as the primary donor and secondary acceptor, respectively; while pyrene (2 or T) unit, having spectral overlap with both 1 and 3, was used as the primary acceptor as well as the secondary donor. Results of time resolved and steady-state emission studies reveal that sequential resonance energy transfer (FRET 1 → 2 → 3) and direct resonance energy transfer (FRET 1 → 3) processes are operational simultaneously. In the sequential energy transfer process (1 → 2 → 3) of the triad system, pyrene acts as a transmitter and makes the whole supramolecular assembly behave as a linear energy transferring wire. Sensitised emission of the coumarin moiety, i.e. the secondary and eventual final acceptor, offers the possibility of evaluating the performance of this linear trichromophoric system by one and two-step FRET mechanisms. Formation of an interwoven complex between the host (NCC24O8) and the guest (T) components, utilizing various non-bonding interactions (intercomponent [N+–H⋯O], [C–H⋯O] and π–π stacking interactions) has been confirmed by 1H NMR studies in solution and a single crystal X-structural study in the solid state. The formation constant (Kf = 2.31 × 103 M−1) for the [2]pseudorotaxane was evaluated using isothermal titration calorimetric studies. The complex gives rise to the first crystal structure of a self-assembled [2]pseudorotaxane that demonstrates sequential two-step FRET based energy transfer in a self-assembled triad that is held in an assembly through non-covalent interactions, such as hydrogen bonding and π–π stacking.

New chemodosimetric probe for the specific detection of Hg2+ in physiological condition and its utilisation for cell imaging studies - Saha, Sukdeb; Agarwalla, Hridesh; Gupta, Hariom; Baidya, Mithu; Suresh, E.; Ghosh, Sudip K.; Das, Amitava (Dalton Transactions, 2013)
A dithiane derivative of BODIPY is synthesized. This new reagent could be used for the specific and instantaneous detection of Hg2+ in physiological condition. This dithiane reagent reacts specifically with Hg2+ to regenerate the parent BODIPY-aldehyde with consequential change in visually detectable optical responses and this provides the possibility of using this reagent as a colorimetric probe or as a fluorescent biomarker/imaging reagent. Further, non-covalent interactions could be utilized for formation of an inclusion complex with biologically benign beta-cyclodextrin for enhancing its solubility in aqueous environment and this included adduct could be used as a fluorescent marker and imaging reagent for Hg2+. Uptake of Hg2+ ions in live HeLa cells, exposed to a solution having Hg2+ ion concentration as low as 2 ppb, could also be detected by confocal laser microscopic studies.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).